2017
DOI: 10.1111/jocn.14058
|View full text |Cite
|
Sign up to set email alerts
|

What impact does nursing care left undone have on patient outcomes? Review of the literature

Abstract: Aims and objectivesSystematic review of the impact of missed nursing care on outcomes in adults, on acute hospital wards and in nursing homes.BackgroundA considerable body of evidence supports the hypothesis that lower levels of registered nurses on duty increase the likelihood of patients dying on hospital wards, and the risk of many aspects of care being either delayed or left undone (missed). However, the direct consequence of missed care remains unclear.DesignSystematic review.MethodsWe searched Medline (v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
304
0
14

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 327 publications
(350 citation statements)
references
References 35 publications
6
304
0
14
Order By: Relevance
“…Our findings enrich the empirical evidence that nurse staffing and missed care impact patient safety, quality of care, and patient and nurse outcomes (Ball et al, 2014;Ball et al, 2017;Cho et al, 2016;Jones et al, 2015;Lake et al, 2016;Recio-Saucedo et al, 2017;Tschannen et al, 2010). The finding that perceived staffing adequacy had significant relationships with all dependent variables, unlike the patient-to-RN ratio, indicates that perceived staffing adequacy may be more sensitive to the overall workload than the staffing ratio, because it reflects the effect of additional factors other than the staffing ratio.…”
Section: Extensive Family Involvement In Inpatient Care As In Korea Andsupporting
confidence: 77%
See 1 more Smart Citation
“…Our findings enrich the empirical evidence that nurse staffing and missed care impact patient safety, quality of care, and patient and nurse outcomes (Ball et al, 2014;Ball et al, 2017;Cho et al, 2016;Jones et al, 2015;Lake et al, 2016;Recio-Saucedo et al, 2017;Tschannen et al, 2010). The finding that perceived staffing adequacy had significant relationships with all dependent variables, unlike the patient-to-RN ratio, indicates that perceived staffing adequacy may be more sensitive to the overall workload than the staffing ratio, because it reflects the effect of additional factors other than the staffing ratio.…”
Section: Extensive Family Involvement In Inpatient Care As In Korea Andsupporting
confidence: 77%
“…Missed care occurs when nurses are required to perform multiple activities at the same time and cannot engage in some nursing activities under conditions of time scarcity. Empirical evidence has suggested that poorer nurse staffing was associated with an increase in nurse-reported missed care, and increased missed care was associated with nurse-reported quality of nursing care and patient safety, adverse events, mortality, and patient satisfaction Jones et al, 2015;Lake, Germack, & Viscardi, 2016;Recio-Saucedo et al, 2017). Empirical evidence has suggested that poorer nurse staffing was associated with an increase in nurse-reported missed care, and increased missed care was associated with nurse-reported quality of nursing care and patient safety, adverse events, mortality, and patient satisfaction Jones et al, 2015;Lake, Germack, & Viscardi, 2016;Recio-Saucedo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Broad measures of missed care make no distinction between the relative importance of the care that is missed. Not all missed care is of equal significance and impact on patient outcomes will vary (Recio‐Saucedo et al., ). While there is some evidence that missed care mediates the relationship between staffing levels and measures of patient satisfaction (Bruyneel, et al., ) and falls (Kalisch et al., ), direct evidence of omitted clinical care mediating the relationship between staffing and mortality is absent (Jones et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Although nurse reports of missed care are associated with adverse patient outcomes (Recio‐Saucedo, et al. ), it remains unclear to what extent these reports correlate with actual omissions of care. While studies that failed to show significant associations were typically smaller and had a higher risk of bias, those which used patient reports did not clearly confirm the results of studies which used nurse reports.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of nurses who reported that skin care was missed during their most recent shift varied between 20.5% and 39.5% . Inadequate skin care is associated with complications, such as pressure ulcers and incontinence‐associated dermatitis (IAD) …”
Section: Introductionmentioning
confidence: 99%